Composição de espécies de lianas e sua resposta ao corte em um fragmento de floresta estacional semidecidual, Araras, SP - Rocha, Elisangela Xavier da (Universidade Federal de São Carlos, 2014)
Although the knowledge on plant richness of seasonal semideciduous forests has been increased during the last years, we have little information about the composition of lianas species in these phytophysiognomies, especially if one consider the small and degraded ones. In this sense, we sampled the species of lianas, and also their abundances and mechanisms of climbing in a 12.8 ha seasonal semideciduous forest fragment located at Centro de Ciências Agrárias (CCA), University of São Carlos (UFSCar), Araras, São Paulo, southeastern Brazil (22º18 00 S and 47º23 03 W). During one year (from March 2013 to March 2014) we registered the liana species through unsystematic hikes in the area. We found 34 species of lianas (14 families and 23 genera). Sapindaceae and Bignoniaceae were the families with the greatest species richness, eight species each one. We classified Serjania caracasana and S. laruotteana (Sapindaceae) as abundant because they occurred throughout the forest area. On the other hand, we found that Schnella microstachya (Fabaceae), Tynanthus fasciculatus (Bignoniaceae), and S. tristis were considered as rare . Species of lianas with tendrils were the most common in the community (64%), followed by the fickle lianas (24%) and the scandent ones (12%). Although small, degraded and isolated, we argued that these forest communities might present a great part of lianas richness, once they have ecosystem features that favor this life form. These findings may represent the basis for the proposition of management routes of the seasonal semideciduous forests; for example, if one should choose between the selective management of lianas or their unrestricted cutting in such ecosystems.
Floristic composition of lianas in a seasonal semideciduous forest fragment in southeastern Brazil
Keywords: Agroecologia; Manejo; Florística; Ecologia; Plantas lenhosas; Floresta tropical; Fragmentação; Hábito trepador; Inventário; Communities; Tropical forest; Floristic; Fragmentation; Climbing; CIENCIAS AGRARIAS